RELATIONSHIP OF PROVISION OF IRON (Fe) TABLETS TO HEMOGLOBIN (Hb) LEVELS IN ADOLESCENT WOMEN AT PUSKESMAS KABILA KAB. BONE BOLANGO: RELATIONSHIP OF PROVISION OF IRON (Fe) TABLETS TO HEMOGLOBIN (Hb) LEVELS IN ADOLESCENT WOMEN AT PUSKESMAS KABILA KAB. BONE BOLANGO - sulastri ismail (Journal of Health, Technology and Science (JHTS), 2020)
This study aims to determine the relationship of giving Fe tablets to hemoglobin levels in adolescent girls.The research method uses a quantitative analytic approach. The type of data used is primary data, namely the results of giving Fe tablets to hemoglobin levels in adolescent girls and secondary data obtained from data from the Kabila Health Center and the Gorontalo Provincial Health Office. The sampling technique in this study used a purposive sampling technique with a total sample of 26 people.The results showed that there was a significant relationship between Fe tablets and Hemoglobin levels, namely 0.04 more <0.05. The average hemoglobin level of adolescent girls aged 15-17 years was obtained at the Kabila District Health Center. Bone Bolango is 12.4 g/dL. The conclusion of this study is that there is a significant relationship between Fe tablets and hemoglobin levels, which is 0.04 more than 0.05. suggestions for further researchers, it is better for further researchers to conduct further research on other factors that affect hemoglobin levels.